Development and testing of a continuous power operated coconut husker - ANU S. CHANDRAN; Dr. Jayan P.R (Guide) (Tavanur 2012 Department of Farm Power Machinery and Energy)
Development and testing of a continuous power operated coconut husker
Development and testing of a continuous power operated coconut husker